Ethnicity in prisons (Academic Journal of Internal Affairs, 2012)
The cultural anthropology-based research focuses on how prisoners create ethnic boundaries, and what characteristics are attributed to group members. The author argues that even though in certain cases ethnicity can be overruled by emphasizing local or other community membership, it is still crucially importance.
Keywords: ethnicity; prison; Roma people